Association between Maternal Knowledge of Personal Hygiene with the Incidence of Diarrhea in Toddlers at Palangka Raya - Adelgrit Trisia; Andine Putri Savindra; Albert Valentino Indrawan (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2025)
Diarrhea is still one of the main causes of morbidity and death in children under five, with mothers' knowledge of personal hygiene playing an important role in children's health. This study aims to examine the relationship between the level of maternal knowledge about personal hygiene and the incidence of diarrhea in toddlers at the Imelda Workers Indonesia General Hospital, Medan. The method used was descriptive with a cross-sectional approach, involving the population of all mothers who had toddlers aged 1-5 years at the hospital. A sample of 50 respondents was taken using a purposive sampling technique, with data collection using a questionnaire and analysis using the Chi-Square test. The research results showed that almost all mothers who had good knowledge about personal hygiene did not experience diarrhea in toddlers. Statistical analysis showed a p value <0.05, indicating a significant relationship between maternal knowledge about personal hygiene and the incidence of diarrhea in toddlers. In conclusion, the better the mother's knowledge about personal hygiene, the lower the incidence of diarrhea in toddlers